HUBUNGAN STATUS BEKERJA DENGAN TINGKAT DEPRESI PADA LANJUT USIA DI JEMAAT GMIM KYRIOS KAWILEY KECAMATAN KAUDITAN MINAHASA UTARA - Manoppo, Melisa Linda; Wungouw, Herlina; Kallo, Vandri D (JURNAL KEPERAWATAN, 2017)
Abstract : Employment status is one of the risk factors for depression. According to World Health Organization (WHO) 2009, the overall prevalence of depression in elderly generally varies between 10%-20%, this number could also change depends on the cultural situation in each region of the world. The purpose of this research is to identify the relationship between employment status with the level of depression in the elderly people at GMIM congregation Kyrios Kawiley, Kauditan District of North Minahasa. The research design used is cross sectional. 56 samples from the elderly were taken by purposive sampling on the 5th of December 2016 at GMIM congregation Kyrios Kawiley Kauditan District. The samples then were analysed using two type of analysis which are univariate and bivariate. The Univariate analysis uses proportion test and bivariate analysis uses chi-square test. The research shows that 53,6% elderly people are employed and 46,4% elderly people are unemployed. Furthermore, 66,1% elderly people have moderate depression while 33,9% of them have mild depression. From the test results obtained from Chi-square test, it is clear that the p value is less than 0,05 (p<0,05). This indicates that there is a significant relationship between employment status with the level of depression in elderly people at GMIM congregation Kyrios Kawiley. In conclusion, there is a relationship between employment status with the depression level of the respondents at GMIM congregation Kyrios Kawiley, Kauditan District of North Minahasa. The suggestion from this research is expected to be useful to nursing science and to be used for feedback in order to improve scientific information about depression in the elderly people. In addition, the suggestion in particular can be applied to the gerontic course. Keywords: employment status, the elderly, depression Abstrak : Status bekerja merupakan salah satu faktor resiko terjadinya depresi. Berdasarkan World Health Organization (WHO) 2009, prevalensi keseluruhan kejadian depresi pada lansia secara umum bervariasi antara 10-20% hal ini juga tergantung pada situasi budaya di masing-masing daerah di dunia. Tujuan penelitian ini adalah untuk mengidentifikasi Hubungan Status Bekerja dengan Tingkat Depresi pada Lanjut Usia di Jemaat GMIM Kyrios Kawiley Kecamatan Kauditan Minahasa Utara. Desain Penelitian yang digunakan adalah cross sectional. Sampel berjumlah 56 lansia, pada tanggal 05 Desember 2016 di Jemaat GMIM Kyrios Kawiley Kauditan yang diambil secara purposive sampling. Analisa univariat menggunakan uji proporsi dan analisa bivariat menggunakan uji Chi-square. Hasil Penelitian menunjukkan lansia yang bekerja sebesar 53,6% dan yang tidak bekerja sebesar 46,4%. Sedangkan lansia yang depresi sedang 66,1% dan yang depresi ringan 33,9%. Dari hasil uji Chi-square didapat bahwa nilai p < 0,05 menunjukkan bahwa terdapat hubungan yang signifikan antara status bekerja dengan tingkat depresi pada lansia di Jemaat GMIM Kyrios Kawiley. Kesimpulan yaitu ada hubungan antara status pekerjaan dengan tingkat depresi responden di Jemaat GMIM Kyrios Kawiley Kecamatan Kauditan Minahasa Utara. Saran Penelitian ini diharapkan dapat bermanfaat bagi ilmu Keperawatan dan dapat digunakan untuk masukan dalam rangka meningkatkan informasi ilmiah tentang depresi pada lansia. Khususnya dapat diterapkan pada mata kuliah gerontik. Kata kunci: status bekerja, lansia, depresi